Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1987
DOI: 10.1128/jvi.61.6.1861-1866.1987
|View full text |Cite
|
Sign up to set email alerts
|

Sequences responsible for erythroid and lymphoid leukemia in the long terminal repeats of Friend-mink cell focus-forming and Moloney murine leukemia viruses

Abstract: Despite the high degree of homology (91%) between the nucleotide sequences of the Friend-mink cell focus-forming (MCF) and the Moloney murine leukemia virus (MuLV) genomic long terminal repeats (LTRs), the pathogenicities determined by the LTR sequences of the two viruses are quite different. Friend-MCF MuLV is an erythroid leukemia virus, and Moloney MuLV is a lymphoid leukemia virus. To map the LTR sequences responsible for the different disease specificities, we constructed nine viruses with LTRs recombinan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
40
0

Year Published

1989
1989
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(42 citation statements)
references
References 34 publications
2
40
0
Order By: Relevance
“…Both SL3 and Mo-MuLV induce T-cell lymphomas in mice. LTR enhancer sequences are crucial determinants of this property (15,27,35,41,50,52,64,98). They appear to act at multiple steps in the process of lymphomagenesis, including viral replication in hematopoietic tissues, preleukemic hyperplasia, and proto-oncogene activation (5,8,9,19,21,25,38,64,78,97).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both SL3 and Mo-MuLV induce T-cell lymphomas in mice. LTR enhancer sequences are crucial determinants of this property (15,27,35,41,50,52,64,98). They appear to act at multiple steps in the process of lymphomagenesis, including viral replication in hematopoietic tissues, preleukemic hyperplasia, and proto-oncogene activation (5,8,9,19,21,25,38,64,78,97).…”
Section: Discussionmentioning
confidence: 99%
“…Transcriptional enhancers located within the long terminal repeats (LTRs) are the primary genetic determinants of the pathogenicity of murine leukemia viruses (MuLVs) (14,15,20,27,41,50,52,98). These elements determine the viral potency and the tissue specificity of viral leukemogenicity (13,85,92,98,105).…”
mentioning
confidence: 99%
“…These results indicate that either M-MuLV has additional determinants of T-cell lymphomagenicity in addition to its enhancers or SRS MuLV has additional determinants for the broad disease spectrum in addition to its enhancers or both. Other investigators have shown that replacement of the M-MuLV enhancers with F-MuLV enhancers is sufficient to convert the disease specificity to erythroleukemia (10,11,26,28,30,47). Therefore, if other T-cell lymphomagenic determinants exist outside the LTR of M-MuLV, they must be relatively weak.…”
Section: Discussionmentioning
confidence: 99%
“…Another well-studied example is the enhancer from the Moloney MLV, which determines the selectivity of the Moloney virus for inducing T-cell lymphomas. Substitution of the Moloney virus enhancer with that from the erythroleukemogenic Friend MLV switches the disease specificity of Moloney MLV from T-cell lymphoma to erythroleukemia (9,10,22,31,38).…”
mentioning
confidence: 99%